2010
DOI: 10.1590/s0074-02762010000600004
|View full text |Cite
|
Sign up to set email alerts
|

Residual effect of a micro-encapsulated formulation of organophosphates and piriproxifen on the mortality of deltamethrin resistant Triatoma infestans populations in rural houses of the Bolivian Chaco region

Abstract: The Bolivian Chaco is part of the endemic region of Chagas disease and an area where pyrethroid resistant Triatoma infestans (Hemiptera: Reduviidae) populations has been reported. The World Health Organization identified these resistant populations as an important focus for research. The objective of this study was to evaluate the residual effect of a micro-encapsulated formulation containing organophosphate active ingredients and a juvenile hormone analogue (Inesfly 5A IGR) on the mortality of T. infestans. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Previous data showed that resistance of domestic T. infestans to deltamethrin is widespread, high in Argentina (Vassena & Picollo 2003, Audino et al 2004) and particularly high in Bolivia, where the highest levels of resistance were observed in the department of Tarija (Alarico et al 2010, Germano et al 2010, Lardeux et al 2010). The present results confirmed this tendency, with the highest RR observed in the domestic population of Taiguati (RR = 818), a colony of approximately 25 specimens collected in a henhouse.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous data showed that resistance of domestic T. infestans to deltamethrin is widespread, high in Argentina (Vassena & Picollo 2003, Audino et al 2004) and particularly high in Bolivia, where the highest levels of resistance were observed in the department of Tarija (Alarico et al 2010, Germano et al 2010, Lardeux et al 2010). The present results confirmed this tendency, with the highest RR observed in the domestic population of Taiguati (RR = 818), a colony of approximately 25 specimens collected in a henhouse.…”
Section: Discussionmentioning
confidence: 96%
“…the broad distribution of deltamethrin resistance, with particularly high levels in the south of the country near Argentina (Alarico et al 2010, Lardeux et al 2010.…”
mentioning
confidence: 99%
“…It is considered that vector control failures, are due to high levels of insecticide resistance in this area [18][19][20][21]. In the last few years, more studies demonstrated that the phenomenon of resistance to insecticides in domestic T. infestans populations presents an extensive distribution in southern Bolivia and northern Argentina [21][22][23], with high resistance ratios, and different toxicological profiles [14,18,19,[24][25][26]. Recently, susceptibility and resistance to deltamethrin and fipronil were detected in wild populations of T. infestans from Bolivia [14,27].…”
Section: Introductionmentioning
confidence: 99%
“…1 It is argued that the slow-release mechanisms enable uniform AI surface concentrations with prolonged residual effect, as compared to earlier PP products using a simple admixture of AIs in standard paint formulations. 2 Depending on the chemical action of the embedded AIs, PPs may display different properties, including spatial repellency, contact irritancy, toxicity, insecticide synergy, or insect growth regulation. Importantly, different AIs can be combined in a single PP to ensure different modes of action in one product.…”
Section: Introductionmentioning
confidence: 99%